IMPLEMENTASI PENGEMBANGAN WISATA BAHARI SONTOH LAUT BERBASIS MASYARAKAT DI KECAMATAN ASEMROWO KOTA SURABAYA - Saosang, Munawarsyah; Kurniawan, Badrudin (Publika, 2023)
The city of Surabaya is one of the tourist destinations in Indonesia which is famous for various types of tourism. This has a huge impact on society. This impact is also felt by the coastal community of Sontoh Laut, who in their daily life work as fishermen. This study aims to analyze the implementation of Surabaya City Government policies in supporting the development of Sea Sontoh Marine Tourism and to describe how the Tourism Awareness Group (Pokdarwis) is involved in managing Sea Sontoh Marine Tourism. The type of research used is descriptive with a qualitative approach and data collection methods through observation, interviews, and documentation studies. This study was analyzed using the policy implementation theory from George Edward III which includes four variables, namely communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the development of Sontoh Laut Marine Tourism has not been implemented properly so it has not been able to fulfill these four variables. Furthermore, based on the discussion it can also be seen that community involvement is still minimal, so the existence of the Sea Sontoh Pokdarwis as the manager has not had a significant impact on its role in involving the community in tourism development. Therefore, to be able to realize sustainable tourism must also be accompanied by a synergy between related parties. It is hoped that the government, community, and private sector will continue to foster the community around Sontoh Laut by conducting measurable training and education.